Neuroimaging in Cerebral Small Vessel Disease - Inayatullah Awan, Muhammad Asif Khaskheli, Ali Akbar, Muhammad Munwar Ali, Mumtaz Ali Narejo, Khairunisa Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the role of neuroimaging in cerebral small vessel disease’s diagnosis and treatment. Study Design: Cross-sectional study. Place and Duration of Study: Department of Neurology, Khairpur Medical College, Khairpur Mir’s from 1st January 2022 to 30th September 2022. Methodology: Seventy five patients were enrolled. The patients were divided in to 5 groups depending on a 5 year interval in their age. The cases of CSVD were included suffering from transient ischemic attack (TIA), lacunar syndromes, stoke with subacute symptoms as cognitive as well as motor disturbances. The age of the patients was >45 years. Clinical examination was conducted through standard procedure and each patient underwent brain magnetic resonance index (MRI) imaging. The neuroimaging features including white matter hyperintensities (WMH), lacunar infarcts (LI), enlarged perivascular spaces (EPVS), microbleeds, lacunae, brain atrophy, and subcortical infarcts. Binswanger’s disease, as well as leukoaraiosis, lacunar strokes and cerebral microbleeds (CMBs) were also observed. The MRI used 3.0 MRI system, using 32-channel head coils.The regions scoring was done through Kippss or Dacies score, as well as through MTA-scale, Koedam score, and GCA-scale, ranging within 0-3 points Results: There are more cases of females suffering from CSVD than males, however only in year 70 there was an equal incidence within gender. There was a significance association of CSVD markers with age wherein the WMH has a significant increase in trend with the ascending of year interval. Fazekas scale was applied quantify amount of the white matter T2-hyperintense-lesions which are accredited to CSVD. It was observed that presence of SVD markers in various age stratification showed highest incidence of MTA scale, Koedam score, Kippss/Dacies score and 3 markers numbers The WMH, CMBs, LI and EPVS were observed highest in the age group of 61-65 years while BA was observed highest in 66-70 years of age Conclusion: Neuroimaging techniques prove beneficial in exact and timely diagnosis of cerebral small vessel disease. Increasing age has higher risk of CSVD presented through increase incidence in CSVD markers. Keywords: White matter, Cognitive, Recurrence, Mortality, Etiology